2020
DOI: 10.3390/ijms21051799
|View full text |Cite
|
Sign up to set email alerts
|

Development of pH-Responsive Biopolymeric Nanocapsule for Antibacterial Essential Oils

Abstract: It is generally believed that antibacterial essential oils have the potential to become one of the alternatives in preventing diarrheal diseases of monogastric animals. The disadvantage is their low efficiency per oral due to easy degradation during digestion in the stomach. This study compares the efficacy of chitosan, alginate-chitosan, guar gum-chitosan, xanthan gum-chitosan and pectin-chitosan nanocapsules to the synthesis of pH-responsive biopolymeric nanocapsule for Thymus vulgaris, Rosmarinus officinali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Chitosan, a positively charged polysaccharide, has also been used as a polyelectrolyte complex with polyanionic xanthan gum for the crosslinking encapsulation of essential oils as potential antibacterial agents, with the aim to improve their stability [ 141 , 142 ]. Skalickova et al tested combinations of chitosan with several polysaccharides, including gums (XG, guar, alginate, and pectin), for the nanoencapsulation of essential oils ( Thymus vulgaris , Rosmarinus officinalis and Syzygium aromaticum ) for potential prevention of diarrheal diseases in monogstric farm animals.…”
Section: Gum-based Micro- and Nanoparticles In Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan, a positively charged polysaccharide, has also been used as a polyelectrolyte complex with polyanionic xanthan gum for the crosslinking encapsulation of essential oils as potential antibacterial agents, with the aim to improve their stability [ 141 , 142 ]. Skalickova et al tested combinations of chitosan with several polysaccharides, including gums (XG, guar, alginate, and pectin), for the nanoencapsulation of essential oils ( Thymus vulgaris , Rosmarinus officinalis and Syzygium aromaticum ) for potential prevention of diarrheal diseases in monogstric farm animals.…”
Section: Gum-based Micro- and Nanoparticles In Drug Deliverymentioning
confidence: 99%
“…The release was tested in a non-compendial setting and in general, different essential oil ingredients were released in a different way depending both on the medium pH and formulation, but burst release in 3 h followed by an extended phase was observed. However, nanoencapsulation decreased the antibacterial activity compared to pure essential oils [ 141 ]. A somehow more promising result was achieved by Li et al in a study on cinnamon essential oil encapsulation process based on a Pickering emulsion template.…”
Section: Gum-based Micro- and Nanoparticles In Drug Deliverymentioning
confidence: 99%
“…The experimental results found that chitosan-guar gum is the most suitable nanocapsule for encapsulating EOs (Skalickova et al, 2020). TA B L E 1 Summary of studies on the stimulating responsive release of essential oil…”
Section: Ph-stimulating Responsementioning
confidence: 99%
“…In other experiments, chitosan was combined with sodium alginate, guar gum, and pectin to produce pH‐responsive natural biopolymers. The experimental results found that chitosan‐guar gum is the most suitable nanocapsule for encapsulating EOs (Skalickova et al, 2020). Moreover, in the production of chitosan‐sodium alginate polymer, if the adsorption of essential oil is followed by chitosan coating, a bilayer porous polymer with excellent thermal stability and dual pH‐stimulating response is produced (Thuekeaw et al, 2021).…”
Section: Sustained Controlled‐release Technologies Of Essential Oilsmentioning
confidence: 99%
“…Nanoencapsulation has been discussed with advantages over conventional microencapsulation due to the unique properties provided by the nanosized particle (1–100 nm) and its high surface/volume ratio, increasing the interaction with enzymes and microorganisms. However, there are still some challenges regarding the technology, and economic and regulatory concerns to its implementation in the food industry in relation to several factors, such as the influence of the wall material, the interaction with the food matrix, the behavior of the nanostructure during food processing, and the use of economic and straightforward strategies to obtain the nanostructures [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%